Endovascular Excimer Laser-Assisted Balloon Angioplasty for Infrapopliteal Arteries in Thromboangiitis Obliterans: A Treatment for Acute-Phase TAO - Pu, Hongji; Jiang, Yihong; Wu, Zhaoyu; Lei, Jiahao; Hu, Jiateng; Qiu, Peng; Zhang, Xing; Huang, Qun; Lu, Xinwu; Yin, Minyi; Zhao, Zhen (Frontiers in Cardiovascular Medicine, 2022)
Background Thromboangiitis obliterans (TAO, Buerger's disease) is an inflammatory and obstructive vasculopathy, which leads to limb ischemic rest pain and ulcerations in the acute stage. Objectives This study aimed to assess the feasibility of excimer laser-assisted balloon angioplasty (BA) for patients with acute infrapopliteal TAO. Method This was a single-center retrospective cohort study. In this study, 220 patients with 210 target limbs between January 2012 and September 2021 were involved. Among them, 52 target limbs have received endovascular excimer laser-assisted balloon angioplasty from January 2017. The ankle brachial index (ABI), rest pain score, ulcer, Rutherford classification, and TASC II classification were assessed. The follow-up time was 6 months. Results The technical success rate of laser + BA and BA groups was 71.15 and 65.82% (p = 0.5021), respectively. After intervention, the ABI of two groups were 0.85 ± 0.20 and 0.77 ± 0.20 (p = 0.0419), and the rest pain score was 1.00 ± 1.43 and 1.71 ± 2.25 (p = 0.0449). During the 6 months follow-up, the ABI of two groups was 0.76 ± 0.17 and 0.75 ± 0.23 (p = 0.8539), the rest pain score was 1.43 ± 1.82 and 2.24 ± 2.06 (p = 0.0783), and the ulcer rate was 23.68 and 40.98% (p = 0.0867), respectively. The proportion of patients who were assessed as TASC II C/D or Rutherford 4–6 in laser +BA group was significantly lower than that in BA group, indicating that the former had better efficacy. The rate of critical limb ischemia and restenosis in the laser +BA group was lower than that in the BA group (47.36 vs. 67.22%; 21.05 vs. 34.43%) during follow-up. In the laser + BA group, the reintervention rate was lower than that in the BA group (2.70 vs. 8.20%, p = 0.0425). No serious adverse events (AEs) occurred. Conclusion Excimer laser debulking-assisted angioplasty is a feasible, effective, and safe method to treat acute infrapopliteal TAO.